MATLAB as a Schedule Assistant for UW-Eau Claire's College of Arts and Sciences - Brake, Danielle; Brisbin, Abra; Ericson, Sarah; Rozek, Dylan; Wiskow, Cara; Denman, Brooke (My University, 2018)
Our team created an agent-based program to advise the administration at UW-Eau Claire when a new class should be scheduled. In creating our model, we used MATLAB to parse and analyze the data from the files we were provided. The goal of this project is to improve and ease the decision making process for course scheduling.
Color poster with text and bar graph.
Keywords: Posters; MATLAB; Mathematics; Class schedules